Influence of money politics on credibility of Nigerian general election 2015 in Taraba State - Chul, Abubakar Auwal (2017)
This study is an attempt to identify the extent of the use of money in an election, the strategies of using moneyin electionand how the influence of money politicsaffected the credibility of election in Taraba state 2015 general election in Nigeria.The methodology of this study is founded on the information obtained from primary and secondary sources. Information critically analyzed using narrative method of documentary analysis and logical conclusions drawn from the analysis.The system andgame theories was adopted in this study.It was found outthat,politicians in Taraba state used money during voters’ registration, party primaries, campaign and during the election proper. Also Politicians adopted various means of giving money and other gifts in kind to appeal the conscience of the electorate.Money politics will only place persons with the funds to get admittance to political office and discourage the masses from political leadership due to their financial handicap. Nigeria and Taraba State seems to be at crossroads as 2019 approaches due to the growing anxiety and challenges ahead of the general elections. If the measures and strategies suggested in the work are taken seriously and implemented, Nigeria can make history by conducting free, fair and credible elections devoid of money politics. The study recommends the following: - attitudinal change, transparency, litigation and public enlightenment on the danger of money politics.